EFFECTS OF ZINC, NITROGEN AND VARIABLE TEMPERATURES ON SEEDLING GROWTH OF WHEAT - Alam, S M; Ansari, R; Khan, M A; Ali, M (Biological Sciences - PJSIR, 2002)
4 2 A nutrient culture experiment was conducted to study the effects of Zn (0.0,2.5 and 5.0 mg 1-1, as a source of Zn S0 7H 0), N (0.0,25 and 50 mg 1-1 as a source of NH S0 ) and variable temperatures (25° and 28°C) on seedling growth f wheat 4 4 (cv Mehran-89). The leaf tips burnt and yellowish green coloured leaves were observed irrespective of t he treatments and temperatures. However, such deficiency symptoms were prominent at higher temperatures and at increasing levels of Zn and N. The shoot and root length and fresh and dry weight of shoot increased on the treatment of 2.5 mg 1-1 Zn alongwith 25 mg 1-1 of N at lower temperature whereas, the fresh and dry weight of root decreased on the similar treatments and temperature . At higher temperature , the root and shoot length and their fresh and d ry weight decreased on treatments. It was concluded that at higher temperature alongwith higher levels of Zn and N, the seedling growth decreased , whereas at lower temperature with 2.5, mg 1- 1 of Zn and 25 mg 1-1 N, the growth generally increased.